Some Fresh Water Algae of Eastern Uttar Pradesh, India - Misra, P.K.; Srivastava, A.K.; Prakash, J.; Asthana, D.K.; Rai, S.K. (Our Nature, 2006)
Present communication deals morpho-taxonomic description of 11 fresh water algae belonging to class Chlorophyceae and Bacillariophyceae. Chlorophycean genera are Pediastrum Meyen (1 sp), Cladophora (2 spp), Staurastrum (3 spp), Onychonema (2 spp) and Desmidium (1 sp) while Bacillariophycean genera are Navicula (1 sp) and Rhopalodia (1 sp). Key words: Bacillariophyceae, Chlorophyceae, Eastern Uttar Pradesh, Fresh water algae doi:10.3126/on.v3i1.338 Our Nature (2005) 3: 77-80